Hexapod Performance - Thirumalesh, Priyanka; Malarvezhi, P; Mahato, Ankita; Choudhury, Meghna (International Journal of Engineering and Technology, 2018)
The purpose of this project is to build a six legged walking robot, which is able to perform basic tasks like walking in the forward direction, backward, moving itâ€™s body up and down and rotating. This project involves designing the hexapod on CAD software Solid Works followed by fabrication and required electronic connections and testing. Due to the stability and its wide flexibility to move in irregular surfaces, hexapod can be very useful in the zones where the natural disasters and also in the aftereffects of the war scenario. The complexity and performance of the hexapod can be widely increased by adding additional sensors and also it can be modified in such a way that it can be used in fields of defense, manufacturing automation and can widely replace the humans in hazardous environment.Â Â